2007
DOI: 10.1002/chir.20438
|View full text |Cite
|
Sign up to set email alerts
|

Direct high‐performance liquid chromatographic separation of the enantiomers of an aromatic amine and four aminoalcohols using polysaccharide chiral stationary phases and acidic additive

Abstract: The HPLC enantiomeric separation of N-benzyl-alpha-methyl-benzylamine, phenylalaninol, tryptophanol, 2 (diphenylhydroxymethyl)pyrrolidine, and isoproterenol was accomplished in the normal-phase mode using two polysaccharide-derived chiral stationary phases (CSPs) and various n-hexane/2-propanol mobile phases with acidic (TFA) or basic (DEA) additive. The compounds were separated without any derivatization and separation factor range between 2.09 and 1.09 with resolution factor 3.4 and 0.4, respectively. The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…A similar effect was noted by us for N-benzyl-a-methylbenzylamine and phenylalaninol using the same CSP. 22 This finding is consistent with a dedicated study on the memory effect of the mobile phase additives on a Chiralpak AD column. 29 Chromato- Table 2.…”
Section: Results Obtained Using Chiralpak Ad Csp With Ethanol As Modisupporting
confidence: 91%
See 2 more Smart Citations
“…A similar effect was noted by us for N-benzyl-a-methylbenzylamine and phenylalaninol using the same CSP. 22 This finding is consistent with a dedicated study on the memory effect of the mobile phase additives on a Chiralpak AD column. 29 Chromato- Table 2.…”
Section: Results Obtained Using Chiralpak Ad Csp With Ethanol As Modisupporting
confidence: 91%
“…22 The g-aminoalcohols in Table 1 actually behave as amines. The acidic additive forms an ion pair with the amine group, and this complex has more effective interactions with the helical cavity of the AD column.…”
Section: Results and Discussion Results Obtained With Chiralpak Ad Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently an independent solid-state NMR study confirmed that 2-propanol displaces hexane more efficiently from the polymeric selector, forming more ordered ''solvent-CSP complexes'' [54]. In order to achieve reproducible results, when switching from an additive-free to an additive-containing mobile phase (e.g., 0.1% trifluoroacetic acid or diethylamine), and vice versa, a prolonged equilibration time may be required [55]. In order to achieve reproducible results, when switching from an additive-free to an additive-containing mobile phase (e.g., 0.1% trifluoroacetic acid or diethylamine), and vice versa, a prolonged equilibration time may be required [55].…”
Section: Polysaccharide-based Cspsmentioning
confidence: 99%
“…키랄 아민 화합물을 광학분리 하는데 있어서 소량의 아민을 이동상에 첨가하는 이유는 분 석물질인 아민과 고정상의 실리카와의 비특이성 상호작용 을 (non-specific interaction) 최소화하여 분석물질의 머무름 시간을 줄여주거나 또는 피크가 꼬리끌기 (tailing) 되어 용리 되는 것을 막아주는 효과를 가지고 있기 때문이다 [7]. 그런 데 몇 연구그룹에서 키랄 아민을 광학분리할 때 소량의 아민 을 염기 첨가제로 이동상에 가하여 분석하는 일반적인 분석 법대신에 산을 첨가제로 사용한 광학분리 결과를 보고하였 다 [7][8][9][10] …”
Section: Introduntionunclassified